A new design proposal and thermal analysis of subassemblies inside a satellite - Sorin Drăghici (Scientific Bulletin of Naval Academy, 2019)
In this study, the authors aim to validate the use of CFRP composites in a subassembly of a satellite as a replacement for currently used aluminum. Considering the high costs of sending a mass unit of payload into orbit, the mass should be minimized. Therefore, the application of composite materials in electronics housing structures was proposed. For this, a new design is proposed and a comparative thermal analysis of the two boxes is made. The present study focusses on a subassembly’s surfaces and materials of a satellite structure subject to thermal variations in order to numerically validate the new design. A satellite electronic housing was subject to a three-dimensional finite element analysis. The satellite’s thermal loading in an orbit of sun-tracking mode is partially transferred to the electronic housing inside. A model is developed and the temperature distribution in the satellite subassembly predicted using empirical available data. Based on the numerical results conclusion and discussions are drawn.